National Identity and the Problem of Kastom in Vanuatu - Tonkinson, Robert (The Australian journal of anthropology, 1982)
Vanuatu's transformation into a predominantly Christian country entailed the loss of much traditional culture and the devaluation of the pre-contact era. In the 1970s the growing independence movement used kastom as a rallying cry to evoke a distinctive non-European national identity. In promoting unity and solidarity, the movement's leaders promulgated kastom on a safe ideological plane, avoiding any definition or differentiation of the concept, whereas the populace attempted to interpret kastom pragmatically. This led to confusion and difficulties because kastom is so ambiguous; its capacity to unite at one level is offset a t others by its political utility in defining difference and in marking boundaries. For Christians, a major problem has been to reconcile the new positive view of kastom with long- entrenched negative attitudes. For the nation-builders, the challenge has been to uphold the virtues of kustorn-within-Christianity while avoiding as much as possible its inclusion in legal codes or in structures and strategies associated with Vanuatu's functioning as a Pacific republic.